Transforming troubled lives strategies and interventions with children with social, emotional and behavioural difficulties - Visser, John, 1946-; Daniels, Harry; Cole, Ted. (Bingley, U.K. : Emerald, 2012)
As inclusive practice becomes more embedded in the policy and practice of schools around the globe, there remains groups of children and young people for whom education is a problem because of the behaviours, poor emotional development and lack of social skills. These pupils often display disaffection towards education and are to be found on the margins of mainstream schools too often they dropout of schooling altogether. Drawing on papers and discussions at the third International Conference of SEBDA in 2010 at Keble College ,Oxford, UK, the papers in this volume both describe and critically examine strategies and interventions in meeting the educational and well being needs of these children and young people. The contributions provide insights into the ways in which these pupils can remain engaged, or even be persuaded to re-engage, in education provided in both mainstream and specialist schools.
Developing emotional literacy : approaches for staff and students developing an approach in the SEBD school / Tina Rae -- At-risk children's attitudes towards the quality of school life / Vera Vojtová, Petr Fucík -- The PALS school-wide positive behaviour support model in Norwegian primary schools : implementation and evaluation / Terje Ogden, Mari-Anne Sørlie, Anne Arnesen, Wilhelm Meek-Hansen -- National behaviour support service and occupational therapy in school : an Irish experience / Siobhan MacCobb -- The school behaviours rating scale : a measure to assess behavioural strengths and needs and inform supportive programming / Lyn Gardon -- Developing staff skills through emotional literacy to enable better practices with children with social emotional and behavioural difficulties (SEBD) / Christiana Koundourou -- Changing professional culture : what nurture groups can achieve / Jim Rose -- Setting up a nurture group in your secondary school / David Colley -- Preventing teacher burnout : exploring the perceptions of teachers for children with social, emotional and behavioural difficulties (SEBD) in Thailand / Saengduean Yotanyamaneewong, Sham Juhari -- The integration of socially disadvantaged pupils in the Czech Republic : a qualitative view on a quantitative phenomenon / Jirí Nemec, Lenka Gulová -- Elective home education : supporting access to education for children and young people within the gypsy, roma and traveller community / Rebecca Clavell-Bate -- Experiencing physical education through the filter of social, emotional and behavioural difficulties / Richard Medcalf -- Professional development : three case studies in residential homes : a holistic personal development programme / Penelope Moon -- A north east pupil referral unit's response to the challenge of NEETs / Crispian Woolford -- Peer massage in the classroom / Jean Barlow -- "It wasnae (only) me" : the development of self-regulation and self-responsibility in pupils experiencing social and emotional behavioural difficulties / Joan Gaynor Mowat -- The challenge for the square peg and the round hole : a sense of belonging to school / Polly Sills-Jones -- Making schools fitting places for all : a creative approach for girls excluded from mainstream education / Melanie Nind, Georgie Boorman, Gill Clarke -- Developing preventative responses to disruptive and high-risk behaviours / Martha J. Holden, Jack C. Holden, Sandy Paterson -- School shooters : monsters or victims / Marcel Lebrun -- SEBDS and the mental processing biases suggested by school-based data collection with children aged 8-12 in Greece : an important finding and suggestions for future research / Christos Papakyriakopoulos -- Early family interventions as prevention of escalation of behavioral and emotional problems in internationally adopted children / Irene Feigin -- The "F" factor : the positive impact of working in partnership with families / Alison Grimshaw -- Punitive trends in Germany : new solutions for deviant behaviour or old wine in new bottles? / Birgit Herz.
Includes index.
Print version record
Keywords: Education -- Special Education -- General; Education -- Special Education -- Learning Disabilities; Teaching of specific groups & persons with special educational needs; Teaching of students with emotional & behavioural difficulties; Learning disabilities; Children with disabilities -- Education; Behavior disorders in children